Espacialização da produção de florestas de Tectona grandis L. f. - Oliveira, Pedro Paulo Gomes de (2019)
Due to the increased availability of technologies, forestry companies are constantly changing their operational and administrative models in order to obtain information that assists forest management in optimizing natural resources and productivity. Thus, the objective of the work was to integrate forest simulation software to Geographic Information System (GIS) software to spatialize the growth and production of a T. grandis plantation in Alta Floresta, Mato Grosso state. The SisTeca simulator has its own equations for site, volume and taper, but allows the user to work with other models. Thus, to perform the simulations with better precision, it was necessary to adjust equations (site, volume and taper). The data used to fit the models come from permanent plots and 139 trees accurately cubed by the Smalian method. In order to verify the quality of the growth and production estimates (prognose) obtained with the adapted SisTeca software, the results obtained with the simulator were compared with the results observed in the inventory and with the results obtained with the original SisTeca. The equations evaluated showed good adjustment and precision results and were used to adjust the SisTeca software, and then to execute the growth and forest production projections. Afterwards, the results obtained with the simulator were incorporated into a GIS software, this integration made feasible the construction of a system that allows the spatialisation of simulated forest production results. Based on the spatial distribution, it was possible to identify different sites in terms of productivity, making possible the adoption of silvicultural and management techniques in a manner appropriate for each identified production unit, taking into account the peculiarities of each area. The spatial analyzes carried out in the present study, as well as the numerous options for manipulating and updating the database, demonstrate the potential of integrating the forest simulator with the GIS software as a support tool for forest management and planning.